Problem-based learning (PBL): Getting the most out of your students - Their roles and responsibilities: AMEE Guide No. 84 - Bate, Emily; Hommes, Juliette; Duvivier, Robbert; Taylor, David C. M. (Medical teacher, 2014)
This Guide discusses the considerable literature on the merits or shortcomings of Problem-based learning (PBL), and the factors that promote or inhibit it, when seen through the eyes of the student. It seems to be the case that PBL works best when students and faculty understand the various factors that influence learning and are aware of their roles; this Guide deals with each of the main issues in turn. One of the most important concepts to recognise is that students and Faculty share the responsibility for learning and there are several factors that can influence its success. They include student motivation for PBL and the various ways in which they respond to being immersed in the process. As faculty, we also need to consider the way in which the learning environment supports the students develop the habit of life-long learning, and the skills and attitudes that will help them become competent reflective practitioners. Each of these elements place responsibilities upon the student, but also upon the Faculty and learning community they are joining. Although all of the authors work in a European setting, where PBL is used extensively as a learning strategy in many medical schools, the lessons learned we suggest, apply more widely, and several of the important factors apply to any form of curriculum. This Guide follows on from a previous review in the AMEE Guides in Medical education series, which provided an overview of PBL and attempts to emphasise the key role that students have in mastering their subject through PBL. This should render the business of being a student a little less mystifying, and help faculty to see how they can help their students acquire the independence and mastery that they will need.